Ormas in the Circle of Brokerage Clientelism: Ormas Brokerage Clientelism Model in Bali General and Local Elections. - Muhammad Ali Azhar (Journal of Politics and Policy, 2019)
Elections or post-conflict local elections in Indonesia always leave interesting things that are never quiet from the discussion in the study of political science. This happens because the elections or local elections held since the revolving reforms have become an arena for the growth of new political actors, both as institutions, groups, or individuals who happen to have the same desire to control political institutions such as; political parties, parliaments, and regional heads. Initiated by the interests of looking for business profit (rent seeking) in the economic sector as a result of the jingling of the dollar in the tourism sector, to the desire to get positions or important positions in these institutions, until then feel the pleasure of seizing and obtaining these sources of power . This is one that was carried out by a number of mass organizations in Bali during the election and post-conflict local elections. By utilizing the clientelism pattern, each of the mass organizations succeeded in placing its candidates to sit in a number of political positions. The purpose of this paper is to explain the phenomenon of the emergence of new clientelism, namely clienteler's Brokerage conducted by several mass organizations in Bali during the implementation of elections and post-conflict local elections. By using a qualitative research method with a descriptive-explanatory type, this paper notes that the clientelism pattern carried out by a number of mass organizations in Bali is not a pure clientelism pattern, but a clientelist pattern that has been modified like a broker, a clientelism pattern that relies on the masculinity of individuals with mass. which is very much to be exchanged for parties, or political officials during the election and post-conflict local elections in order to obtain sources of power. A new clientelism model that emerged as a result of the clientelism practice was carried out by each of these organizations. Key Words: Mass Organizations, Brokerage Clientelism, Election and Bali elections.